Application of natural antioxidants in the composition of gel "Imbirol" for rhinitis of different genesis - Kryzhna, S. I.; Kievskaya, Yu. O.; Kozar, V. V.; Tyupka, T. I. (Journal of Education, Health and Sport, 2018)
One of the stages of the pathophysiological study of the state of the prooxidant-antioxidant system under the conditions of modeling different types of rhinitis in rats was carried out. The experiment took 36 rats, with bacterial and chemical rhinitis, with treatment and without it. Indicators of peroxidation of lipids and antioxidant system were determined in serum: thiobarbituric acid (TBA) and diene conjugates (DK), reduced glutathione (RG) and catalase (Cat). The obtained research results confirmed the formation of oxidative stress in experimental groups, both in chemical and bacterial rhinitis, according to DK and TBA data at 168.3%, 216.1% (chemical) and 159.4%, 216.1% (at bacterial) compared to intact animals. Imbirol shows pronounced therapeutic antioxidant properties in comparison with the reference preparation Pinosol. The effectiveness of the new gel "Imbirol" has a more positive dynamics of AOS restoration in blood serum when developing experimental rhinitis and does not differ significantly from the parameters of the reference preparation "Pinosol". In the pathogenesis of chemical and bacterial rhinitis, the violation of the antioxidant-antioxidant system is installed at the system level. Application of powerful universal treatment with gel "Imbirol" in both types of experimental rhinitis contributes to the normalization of the indicators of the system "peroxidation-antioxidant protection". The applying of the gel "Imbirol" in chemical and bacterial rhinitis reliably led to the restoration of the excited AOS parameters at the systemic level by reducing the concentration of TBA and DC and increasing the activity of the enzymes of catalase and RG. The obtained results allow to continue the study of the influence of antioxidants in experimental rhinitis, and mechanisms of restoration of the nasal mucosa under the pharmacological influence of the gel "Imbirol".